Računalniški kognitivni trening pri otrocih in mladostnikih z lažjo motnjo v duševnem razvoju - Mahne, Nastasija (Psihološka obzorja (Ljubljana), 2021)
Ageing of population and related cognitive decline have contributed to an increased interest in cognitive computer training as one of options for maintaining cognitive abilities. Our research was aimed at verifying how cognitive computer training aff ected cognitive abilities as well as how it was connected with initial cognitive abilities and life satisfaction of active older adults. The research comprised 46 subjects of whom 25 received cognitive computer training and the remainder were assigned to a passive control group. Before and after the intervention, both groups were tested with a test battery which consisted of a demographic questionnaire and objective tests of cognitive abilities. The outcomes showed a statistically signifi cant eff ects of cognitive computer training on visuospatial abilities and attention, as well as on short-term memory and working memory. However, there was no notable diff erence in verbal domain, as had been anticipated. We have also noticed profound eff ects of cognitive computer training on individuals with lower cognitive abilities in visuo-spatial domain, short-term memory, verbal fl uency and information processing speed.
Keywords: children with mild intellectual disability; computerized cognitive training; executive functions; hitrost procesiranja informacij; izvršilne funkcije; kognitivne sposobnosti; memory processing speed; otroci z lažjo motnjo v duševnem razvoju; računalniški kognitivni trening